1979
DOI: 10.1302/0301-620x.61b3.113415
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the anterior talofibular ligament for the treatment of the unstable ankle

Abstract: Chronic instability of the ankle is frequently due to disruption of the fibres of the anterior talofibular ligament and the anterolateral capsule. This allows momentary subluxations at the ankle joint; the talus tilts into an abnormal varus position and rotates forwards and inwards about a vertical axis which passes through the medial malleolus. The use of a free tendon graft to reconstruct the anteriot talofibular ligament restores the stability of the ankle without restricting movement at the subtalar level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 10 publications
2
37
0
Order By: Relevance
“…Pre-and postoperative ankle scores according to Karlsson (1991), Tegner and Lysholm (1985) and Sefton et al (1979) …”
Section: Discussionmentioning
confidence: 99%
“…Pre-and postoperative ankle scores according to Karlsson (1991), Tegner and Lysholm (1985) and Sefton et al (1979) …”
Section: Discussionmentioning
confidence: 99%
“…Before arthroscopy, and 6 months after reconstruction, we assessed the function of the ankle with the squeeze test, the external rotation test, and the fibula translation test, as well as the Tegneractivity level score (Tegner and Lysholm 1985), the Karlsson (1991) score, the Sefton et al (1979) score, and the Ankle-Hindfoot scale (Kitaoka et al 1994). About 6 weeks after the arthroscopy, reconstruction of the anterior syndesmosis was performed by medialization and cranialization of the tibial insertion of the slack anterior tibiofibular ligament, after a syndesmotic set screw was placed during compression of the mortise (Beumer et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…In 1996, Hennrikus et al [86] prospectively compared the modified Broström with the Chrisman-Snook procedure in 40 patients. Both demonstrated improvement in more than 80% of patients, although those who underwent a modified Broström procedure had a lower rate of complications and a higher Sefton [100] outcomes scores. The authors concluded that the modified Broström procedure was superior to the Chrisman-Snook procedure for chronic lateral ankle instability.…”
Section: A B Cmentioning
confidence: 98%